Systematic Literature Review: Dampak Akuisisi Terhadap Kinerja Keuangan Bank Syariah - Hasan Husaini; Badruddin Badruddin; Mahmud Yusuf (Jurnal Ilmiah Ekonomi Islam, 2023)
Study This aim For test the effect of the merger on performance Islamic banking finance in Indonesia. Data used in study This is secondary data form report issued finances by sharia banks that become object research . Method used in study This is descriptive comparative with approach quantitative . Technique data analysis used is test difference between paired sample t-test and analysis comparison ratio finance . Results study show that the merger has different influences to performance Islamic banking finance in Indonesia. A number of study show exists difference significant on ratio finance after the merger is done , which shows enhancement on net NPF, NOM, and BOPO ratios after the merger. However , there is Also research shows that the merger is not give significant impact to performance Islamic banking finance in Indonesia. Results study This show that the effect of the merger on performance Islamic bank finance in Indonesia still need researched more continue . Based on results research that has done , the merger can impact positive or No give impact significant to performance Islamic banking finance in Indonesia. By Because it must consider with ripe decision For Merged and do evaluation to performance finance.